2003
DOI: 10.1093/milmed/168.10.797
|View full text |Cite
|
Sign up to set email alerts
|

The Response of a Bone Resorption Marker to Marine Recruit Training

Abstract: Significant bone resorption took place at the end of Marine recruit training due to accumulation of weight-bearing exercise throughout training and the increase in marching toward the end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This result suggests a potential impact on ARA force generation capacity, especially when considering that some trainees may have been injured to the extent that they did not complete training and as such could not report their injuries in this study. While not specific to load carriage, the literature does suggest that rates of musculoskeletal injuries are higher during the earlier weeks of military training, when untrained recruits are adapting to an increase in exercise (46)(47)(48)(49)(50). Proposed causal mechanisms for these injury patterns vary.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests a potential impact on ARA force generation capacity, especially when considering that some trainees may have been injured to the extent that they did not complete training and as such could not report their injuries in this study. While not specific to load carriage, the literature does suggest that rates of musculoskeletal injuries are higher during the earlier weeks of military training, when untrained recruits are adapting to an increase in exercise (46)(47)(48)(49)(50). Proposed causal mechanisms for these injury patterns vary.…”
Section: Discussionmentioning
confidence: 99%
“…A study in British Army recruits (n = 26) reported a reduction in two markers of bone formation, and a non-significant reduction in the bone resorption marker tartrate resistant acid phosphatase (TRAP) between the start and completion of 10 weeks of initial Army training [19]. Conversely, a study in male (n = 58) and female (n = 155) US Marine recruits measured higher concentrations of the bone resorption marker deoxypyridinoline (DPD) at the end of an 11 week training programme compared with before the start of the training programme [36]. Evans et al observed higher concentrations of serum CTx at middle and end time points, of a 4-month programme of basic recruit training, compared with baseline concentrations in n = 58 male military recruits [21].…”
Section: Bone Resorptionmentioning
confidence: 99%